Hermeneutika Al-Quran Nasr Hamid Abu Zayd: (Studi Kritis Teologis Terhadap Konsep Hermenietika Nasr Hamid Abu Zayd) - masduki, Asyhari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The emergence of hermeneutics as a method of interpreting the Qur'an has raised polemics among Muslims. Even the verdict of infidel was thrown by some groups to the proponents of this method, such as Nasr Hamid Abu Zaid. The verdict of infidel is a term in theology or creed. So it is necessary to conduct in-depth research on the concept of hermeneutics with a theological approach. Because the basis of this method is considered not in line with Islamic creed, even contradictory to Islamic creed. This study tries to analyze the concept of hermeneutics of Nasr Hamid Abu Zayd with the theological approach of Ahlussunnah Wal Jama'ah, using the library research method. This study concludes that it is true that there is a contradiction between the basis of the hermeneutics method and the principles of Islamic creed, which are generally believed by Muslims.